OUTPOURING OF WORKING TIME OF FAMALE FARMERS ON LOWLAND RICE FARMING IN THE VILLAGE OF KUALA TWO SUNGAI RAYA SUBDISTRICT KUBU RAYA REGENCY - PRANSISKUS, PRANSISKUS; ARITONANG, MARISI; IMELDA, IMELDA (Jurnal Sains Mahasiswa Pertanian, 2019)
The agricultural sector in Indonesia is very important in development that is as a source of life and income of farmers in the family. Therefore, efforts to increase production and increase in farmers income need to be developed continuously. This research is aimed to analyze the working hours of women farmers work time and aimed to analyze socio-economic factors that influence the working hours of women farmers work time in paddy rice farming inÂ the villiage of Kuala two, Sungai Raya subdistrict Kubu Raya Regency. The sampling technique used is simple random sampling method. The sample used in this study amounted to 61 female farmers. This study was processed using the SPSS program and then analyzed using multiple linear regression methods. The results showed that age, number of dependents, land area, family income and experience significantly affected womenâ€™s work time in Kuala II village, while the education level did not significantly affect womenâ€™s work time in Kuala II village.Keyword: Multiplie linear regression, The working hours of women farmers